SAS and Special Forces mental toughness training how to improve your mind's strength and manage stress - McNab, Chris 1970- (SAS and Special Forces Series, 2018)
SAS and Special Forces Mental Toughness Training examines what it takes to be as mentally fit as a special forces soldier. The book explains why it is equally important to focus on stress management and mental discipline as it is to concentrate on push-ups, sit-ups and other physical exercises. Using simple steps, the book shows the reader how they can build up their endurance over a matter of weeks and months, and how their quality of life will benefit. SAS and Special Forces Mental Toughness Training demonstrates how you can gain the psychological edge over your opponent, as well as ready yourself for critical challenges ahead. Whether you are competing in unarmed combat sports, running a marathon or just looking to get ahead, SAS and Special Forces Mental Toughness Training will have helpful and practical advice for you. The book includes a number of military training programmes designed to assess a trainee's fitness for the arduous life of a combat soldier, as well as chapters on leadership, battle tactics, escape and survival techniques, and improving intelligence and concentration. SAS and Special Forces Mental Toughness Training is an essential guide to testing and improving mental agility and resilience in the modern combat environment.